Influence of Long-Distance Transportation on Concrete Temperature in Hot Regions and Corresponding Prevention and Control Measures - XIE Ji'an; SHI Chengxiang (Renmin Zhujiang)
The temperature increment during long-distance transportation of concrete in a high-temperature environment is the key difficulty in mass concrete construction and one of the key factors affecting whether the pouring temperature reaches the standard.Against the background of the right bank project of Datangxia Gorge as well as the problem of over temperature in long-distance horizontal transportation during on-site concrete construction,this study makes transformations such as vehicle insulation and stratification.The statistical analysis of the outlet temperature and warehousing temperature tests shows that the temperature increment of concrete during long-distance transportation can be minimized with these transformations,and the average temperature increment is lower than 2 ℃ during high-temperature transportation.The relevant transformation technologies can provide a basis and technical support for concrete construction in a high-temperature environment.